Management of dentoalveolar trauma in adult with nylon splinting and 15 days' delay in treatment-Case report - Sandra Milena Bornacelly Mendoza (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Background and objective: Root fracture is relatively rare and represents only 0.5-7% of all dental trauma, its incidence is higher in children than in adults and depending on the way it occurs it can be vertical or horizontal , which depends on its location in the case of horizontal fracture, it can be generated at the level of the cervical, middle or apical third of the root, which depends on multiple factors such as the delay in treatment, the type of splint used, age, and fixation time, the healing of the separated fragments may be impaired. Traditionally for the management of root fractures, rigid immobilizations were used for long periods of time, however, currently the management has changed towards the use of more flexible splints such as nylon, orthodontic wires, sutures, among others. The objective of this study is to present the case of a 21-year-old male who suffers a motorcycle accident with multiple trauma injuries including subluxation, root fractures combined with complicated coronal fracture, root fracture with extrusive luxation and individual complicated coronal fracture; splinted with nylon and delayed in treatment for 15 days.  Results: it was managed with nylon splinting (fishing line) from tooth 14 to 24 for 25 days with root canal therapy in several teeth; After clinical and radiographic follow-up at 10 weeks, there is evidence of absence of symptoms, return of functionality, different types of segment consolidation despite the delay in treatment and high diastasis of the root fragments.  Conclusion: Early diagnosis with the necessary procedures during trauma management, knowledge of the healing processes and adequate follow-up are key to a correct approach to root fractures.